Keberlanjutan Usaha Peternakan Domba Kisar dan Strategi Pengembangannya di Pulau Kisar Provinsi Maluku - Tatipikalawan, Jomima Martha; Sangadji, Insun (Jurnal Galung Tropika, 2024)
This study aims was to analyze the sustainability index and status of the Kisar sheep business and establish a strategy for the sustainability of Kisar sheep development. This study was implemented in Kisar Island, Maluku Province, using 95 Kisar Sheep farms and 15 expert respondents selected by purposive sampling. The data collection methods are literature study, Focus Group Discussion (FGD), in-depth interviews, and surveys. The research variables are 48 sustainable Kisar sheep development attributes from ecological, sociocultural, economic, technology-infrastructure, and legal-institutional dimensions. The data was analyzed using the Rap-DOMKI coordination technique through the Multi-dimensional Scaling (MDS) method to measure the sustainability indexes and status, Leverage analysis, and Monte Carlo analysis. The study results showed that the business was sustainable in ecological, sociocultural, economic, and technological infrastructure dimensions. However, it needed to be more sustainable in the institutional-legal dimension. It was found that 13 attributes sensitively influence business sustainability. Monte Carlo analysis showed that the difference in the sustainability index value of the five sustainability dimensions was very small or less than one (at a confidence level of 95%), which indicates a high precision level. The MDS Rap-DOMKI analysis showed that the stress value was 13-14% and the coefficient determination (R2) of 0.95. It indicates that the MDS Rap-DOMKI analysis model is adequate for estimating the sustainability of Kisar sheep development. It has a high confidence level and can be used as an evaluation tool for fast analysis of sheep development sustainability in one region.